ØªØÙ„ÙŠÙ„ Ø§Ù„Ù…Ø¹Ù†Ù‰ Ù„ØØ±ÙˆÙ Ø§Ù„Ø¬Ø± ÙÙ‰ Ø³ÙˆØ±Ø© Ø§Ù„Ø¬Ù…Ø¹Ø© - Andri Warseto (Lughatu Ad-Dhat, 2021)
The objectives of this research are to know the divisions of prepositions and their meanings, and then to determine the meaning of prepositions in Surat Al-Jumu`ah. The researcher found in this research twenty letters, they are ba, min, to, on, ali, fi, kaf, lam, wawwassem, ta’a, since, since, lord, even, khala, ada, hasa, ki, perhaps, and when. It is divided into four sections: what is used in the exception, the preposition works as oddity or in a few language, what works in the apparent noun only, and what works in the apparent noun and pronoun. The researcher found in Surat al-Jumu’ah eight letters (from, in, ba, lam, to, on, kaf, and perhaps) that I used in a number of repetitions, until the number reached twenty-nine letters. The letter (from) has seven meanings in this surah which are to denote the circumstance, to denote the circumstance of time, to clarify, to denote the circumstance of the place, the meaning of (from), the adverb twice, and the transcendence twice. The letter (in) has two meanings, which are adverbial four times, and the meaning of (to) one time. The letter (Baa) has three meanings, which are to denote the transitive verb by another twice, for the reasoning once, and for the affirmation twice. The letter (Lam) has three meanings: for the increase twice, for the quasi possession once, and for the end of the end once. The letter (to) has one meaning, which is the end of the goal three times. And the letter (on) has one meaning, which is to sublime. The letter (al-kaf) is a simile, and the letter (al-'ala) is for hope.